Language Policy and Regional Varieties of the Korean Language - Vladislava Mazana (Politeja)
The aim of this paper is to provide information on the language policy, planning, and management in the Republic of Korea. The research is focused on Standard Korean and the current state of Korean regional dialects. Language policy and its effect on regional varieties of Korean language are discussed. Particularly, problems of maintenance and revitalization of regional dialects are described. Included are the efforts towards a language reunion with North Korea and the impact of new technologies.